Effects of Hydration on Gentamicin Excretion and Renal Accumulation in Furosemide-Treated Rats - Chiu, Peter J. S. (1978)
The effect of furosemide on gentamicin excretion and tissue accumulation was studied with clearance techniques in anesthetized rats, at two different infusion rates of saline or Ringer solution. Gentamicin (∼20 mg/kg) was administered by constant intravenous infusion over a period of 3 h. With the low fluid infusion rate, furosemide (25 mg/kg intravenously) caused severe reduction in glomerular filtration rate and diminished urinary output of gentamicin. Serum and renal tissue levels of the antibiotic were significantly elevated. High fluid infusion prevented the decline of the glomerular filtration rate, with near normalization of all measurements. A fluid deficit incurred by furosemide was noted at both the low and high infusion rates. Complete correction of this fluid deficit by continuous adjustment of the infusion rate fully restored normal renal handling of gentamicin. These results suggest that furosemide had no direct effect on renal excretion of gentamicin. In comparison, renal handling of gentamicin in rats did not respond to changes in the rate of fluid infusion in the absence of furosemide therapy. It appears that gentamicin excretion and gentamicin accumulation in the renal cortex in furosemide-treated rats, in contrast with those in untreated rats, are influenced significantly by the rate of fluid infusion. Fluid administration sufficient to maintain the glomerular filtration rate was found to be necessary for appropriate gentamicin elimination, with consequent reduction in serum and renal tissue levels of the drug.